Forging the ideal educated girl: The production of desirable subjects in Muslim South Asia - Adenuga, Taiwo (Journal of Interdisciplinary Studies in Education, 2021)
Shenila Khoja-Moolji’s (2018) Forging the Ideal Educated Girl explores the history of Muslim girls/women in South Asia and their difficulties in acquiring an education. This book piqued my interest because girls’ education is a highly debated topic globally when it comes to the Islamic religion.